Investigating temperature effects on extra virgin olive oil using fluorescence spectroscopy. (14th November 2017) - Saleem, M; Ahmad, Naveed; Ali, H; Bilal, M; Khan, Saranjam; Ullah, Rahat; Ahmed, M; Mahmood, S
Abstract: The potential of fluorescence spectroscopy has been utilized to study the heating effects on extra virgin olive oil (EVOO). Through a series of experiments, a temperature range from 140 °C  −  150 °C has been found where cooking with EVOO is possible without destroying its natural ingredients. Fluorescence emission spectra from all heated and non-heated EVOO samples were recorded using an excitation source at 350 nm, where emission bands in non-heated EVOO at 380, 440, 455, and 525 nm are labelled for vitamin E and a band at 673 nm is assigned for chlorophyll a. The emission band at 525 nm is also responsible for beta carotenoids (vitamin A). As a result of heating, prominent intensity variations have been observed in all spectral bands, but it is particularly affected at 525 nm, indicating the deterioration of vitamin E and beta carotenoids. However, if the temperature of oil can be maintained in the above defined range, then frying food with EVOO is possible by preserving its natural ingredients. The spectral variations resulting from the heating effects have been further highlighted by using principal component analysis for classification purposes.